Manajemen Kearsipan Digital di SMPN 16 Bandar Lampung - Ryan Dwi Prasetya; Ilhami (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
This study was conducted based on the phenomena that often occur in the implementation of digital archival management such as in the stages of archive creation, use of archive storage, archive maintenance and archive reduction that have not been carried out optimally. One of the supporting factors for success in achieving the goals of educational institutions is order in the field of archiving. The implementation of good digital archival management also has a function to facilitate administrative staff in managing school administration. This study uses a qualitative research method that aims to provide a systematic, factual and accurate description of the facts in the field. To obtain and collect the data needed in this study, the author uses several methods, namely observation, interviews and documentation, with data sources obtained from the principal, administration department and teachers of SMP Negeri 16 Bandar Lampung. For data sources, the author uses primary data sources and secondary data sources, then for data analysis, data collection techniques, data reduction, data presentation and drawing conclusions are carried out. Based on the analysis that has been carried out, the results obtained are that at SMP Negeri 16 Bandar Lampung. has implemented digital archiving management quite well, starting from the archive creation stage to the reduction of archives. However, there are several things that need to be considered such as mixed archives because they still use the same building, an archive storage system that still uses a stacked origin system which makes it difficult to find archives again if needed and an archive maintenance system that has not been carried out routinely and the lack of administrative staff that has caused a lack of manpower to separate archives that have been mixed for a long time, therefore it is hoped that the school will pay more attention to the archiving section, especially in the archive life cycle.